Effect of Glyphosate on Guineagrass Submitted to Different Soil Water Potential - SILVA JR.,A.C. (2018)
ABSTRACT: The action of herbicides on weeds that develop under water deficit can be compromised, because the routes of penetration of hydrophilic herbicides are reduced due to the lower hydration of the cuticle in these plants. Moreover, hydrophobic compounds found in the epicuticular wax coating of plants under water stress, hinder the penetration of hydrophilic compounds. This study evaluated the control efficiency of glyphosate on guineagrass plants when submitted to different water deficits. The study was conducted in a greenhouse, and treatments were composed of guineagrass plants submitted to three soil water conditions [low water deficit (13%), intermediate water deficit (10%) and high water restriction (8%)], three doses of glyphosate (0.0, 270.0 and 540.0 g ha-1) and two phenological stages of plant development (4-6 leaves and 1-3 tillers). The water management started when plants presented two developed leaves. Visual evaluations were performed 7, 14, 21 and 35 days after the application of the herbicide; the morpho-physiological parameters of the specific leaf area, stomatal conductance and the difference between the environment temperature and the leaf temperature on the day of the herbicide application were also analyzed at the end of the study, as well as the dry matter of shoot and root. With the increase of the water restriction, there was a decrease in the analyzed morpho-physiological parameters, as well as in the dry matter accumulation of the shoot and roots of the studied plants. Plant control was more efficient when a 540 g ha-1 dose of glyphosate was applied, and when they were controlled at their vegetative stage of 1-3 tiller, and with a water management of 13%. It is possible to state that guineagrass under water restriction have less control efficacy when treated with glyphosate.